2020
DOI: 10.33258/birle.v3i3.1193
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Model for Post-Pandemic Higher Education

Abstract: Education is one of the main sectors that has been drastically affected by COVID-19 pandemic worldwide. In this paper, after providing a brief background about the global impact of Coronavirus pandemic on different spheres of life, the effect of COVID-19 on education, in general, and higher education, in particular, will be discussed. Then, different types of online educational models will be reviewed. Next, the advantages and disadvantages of face-to-face classroom instruction versus online education will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…Following the disperse of Covid-19 globally, to continue as well as to save the academic year, the sole remedy at hand universities, schools, and colleges could consult was online education. However, teachers, students, and even the infrastructure of many educational institutions were not ready for this sudden and unexpected change (Keshavarz, 2020). Then, enormous ways were endeavored to turn education back on its proper path.…”
Section: The Most Implemented Three Models Of Education After Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the disperse of Covid-19 globally, to continue as well as to save the academic year, the sole remedy at hand universities, schools, and colleges could consult was online education. However, teachers, students, and even the infrastructure of many educational institutions were not ready for this sudden and unexpected change (Keshavarz, 2020). Then, enormous ways were endeavored to turn education back on its proper path.…”
Section: The Most Implemented Three Models Of Education After Covid-19 Pandemicmentioning
confidence: 99%
“…According to Wang, Shannon, & Ross (2013), Wilde & Hsu (2019), distant or online education suggests that learners are apparently/physically remote from the teachers and claim a transference type/method. Keshavarz (2020Keshavarz ( , p. 1386) stated: "traditional teaching strategies are practical; however, with advances in educational technology, the effectiveness of traditional learning methods has become something of the past." Despite the usefulness of such a model of teaching and learning, there are many problems associated with it.…”
Section: Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The government also suggested hybrid learning. It combines the traditional and online classroom aspects (Keshavarz, 2020;Sim et al, 2021). Students benefit from this approach as it promotes learning independence, discussion, better teachers' classroom management, material sharing, and learning before class meetings (Ekanayake & Weerasinghe, 2020;Haratikka, 2020).…”
Section: Technology Use In Teaching Literaturementioning
confidence: 99%
“…Furthermore, synchronous learning, especially in video conferences, promoted students' learning engagement more than lecture recordings; therefore, hybrid learning was highly suggested for successful post-pandemic learning. Keshavarz (2020) proposed the methodology for online learning in the post-pandemic era, including online material sharing, online assessment, communication through synchronous and asynchronous platforms, and blended learning. Sim et al (2021) suggested higher education pedagogy, including increasing language skills and improving students' engagement, motivation, and confidence.…”
Section: Technology Use In Teaching Literaturementioning
confidence: 99%